Parkinson’s disease: Certain features of pathology, genetics, and pathogenesis - Hung, Do Manh; Hai Ha, Nguyen; Dang Ton, Nguyen (Vietnam Journal of Biotechnology, 2021)
Parkinson disease (PD) is the second-most common and complex neurodegenerative disorders in humans, characterized by motor symptoms such as tremor, rigidity, bradykinesia, and non-motor symptoms such as insomnia, constipation, anxiety, depression and fatigue. Up to now, the diagnosis of PD has been mainly based on clinical symptoms with motor features being the mainstay and this limits the possibility of early detection. PD is usually diagnosis after the sixth decade of life, however about 5–10% of patients who develop the disease before the age of 50 are early-onset PD. The rapid development of genetic studies and their application may induce the early diagnosis of PD in the near future, especially for the early-onset PD. A few mechanisms have been implicated in PD pathogenesis, with α-synuclein aggregation central to the development of the disease. Multiple other processes are thought to be involved, with several studies suggesting that abnormal protein clearance, mitochondrial dysfunction, and neuroinflammation play a role in the onset and progression of PD. There are many PD patients in Vietnam, however, the studies are mainly based on clinical symtom descriptions. Given the aging of the population, the prevalence of PD is to increase dramatically, which would lead to increased urgency for the need to identify improved methods in diagnosis and treatment this disease.